2007
DOI: 10.4049/jimmunol.179.5.2748
|View full text |Cite
|
Sign up to set email alerts
|

African Trypanosomiasis: Naturally Occurring Regulatory T Cells Favor Trypanotolerance by Limiting Pathology Associated with Sustained Type 1 Inflammation

Abstract: Tolerance to African trypanosomes requires the production of IFN-γ in the early stage of infection that triggers the development of classically activated macrophages controlling parasite growth. However, once the first peak of parasitemia has been controlled, down-regulation of the type 1 immune response has been described. In this study, we have evaluated whether regulatory T cells (Tregs) contribute to the limitation of the immune response occurring during Trypanosoma congolense infection and hereby influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(129 citation statements)
references
References 51 publications
(52 reference statements)
6
120
3
Order By: Relevance
“…Can our prediction be confirmed that a CD8 Ϫ subset of NKT cells promotes proliferation of Tregs in trypanosome infections? Are the regulatory loops between different cell types of the immune system that we are un- After completing this manuscript, we discovered a study on treatment with anti-CD25 Abs of relatively resistant C57BL/6 mice infected with T. congolense (34). The authors report findings and conclusions that differ from ours.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…Can our prediction be confirmed that a CD8 Ϫ subset of NKT cells promotes proliferation of Tregs in trypanosome infections? Are the regulatory loops between different cell types of the immune system that we are un- After completing this manuscript, we discovered a study on treatment with anti-CD25 Abs of relatively resistant C57BL/6 mice infected with T. congolense (34). The authors report findings and conclusions that differ from ours.…”
Section: Discussioncontrasting
confidence: 46%
“…We had recently speculated that Tregs would, via IL-10, down-regulate the immunopathology in infected relatively resistant C57BL/6 mice (14). Guilliams et al (34) have now provided good evidence that Tregs control the immunopathology in T. congolense-infected C57BL/6 mice, with IL-10 being a major mediator. Although they also used administration of anti-CD25 Abs before infection, they did not, as we did, observe an early elimination of the parasites as an effect of the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although initially described to regulate autoimmune responses [13,16,17], it has also been demonstrated that Treg cells can regulate the immune response against infectious agents including parasites [18e21]. In this context, in vivo depletion of CD25 þ T cells was shown to lead to an increase in IFN-g production in mice infected with Plasmodium chabaudi adami [22] and Trypanosoma congolense [23], or in animals infected with Schistosoma mansoni to an increased production of IFN-g, IL-4, IL-5 and IL-13 [24] indicating that Treg cells can control both TH1 and TH2 responses.…”
Section: Introductionmentioning
confidence: 99%